The Influence of Principal Leadership, Work Motivation, and Work Discipline on Teacher Performance: A Quantitative Study in Elementary Schools of Bulakamba District, Brebes Regency - Nurohman, Cahyo; Nurkolis, Nurkolis; Kusumaningsih, Widya (FKIP - Universitas Riau, 2025)
This study examines the influence of principal leadership, work motivation, and work discipline on the performance of elementary school teachers in Bulakamba District, Brebes Regency. Using a quantitative approach with an associative correlational design, the research involved 384 teachers with 196 selected as samples through simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed with multiple linear regression. The results reveal that, partially, principal leadership has the strongest effect on teacher performance with a contribution of 89.6%, followed by work discipline at 43.8% and work motivation at 34.6%. Simultaneously, the three variables contribute 91.1% to teacher performance, indicating a very strong combined effect, while the remaining 8.9% is explained by other factors outside the model. These findings emphasize that teacher performance improvement requires strong leadership, high motivation, and consistent discipline. The novelty of this study lies in integrating these three variables into a single model in the context of elementary schools in rural areas.